Effectiveness Of Core Learning In Terms Of Student Confidence - Nasrulloh, Muhammad Farid; Munhamiroh; Umardiyah, Fitri (SCHOOLAR: Social and Literature Study in Education, 2024)
The Aqidah Akhlak subject is a branch of Islamic Religious Education (PAI). Islamic Religious Education (PAI) is an effort to foster and nurture students so that they can always understand Islamic teachings as a whole. Then live the goal which in the end can practice and make Islam as a way of life. The notion of learning is the process, the way of action makes people or living things learn. The purpose of this research is to the effectiveness of core learning in terms of student confidence in class X Aqidah Akhlak material. This study uses a quantitative approach in the form of a quasi-experimental design (pseudo-experiment). The research instrument used was a problem-solving ability test, student learning independence questionnaires, and observation sheets. Instruments used to measure must be validated to get truly valid data. For validating the test of understanding the moral Aqidah that was carried out was by carrying out validity and reliability tests, as well as analyzing the level of difficulty and determining the differential power of the instrument items. The implications of the results of the research for the practical benefits of research are the influence of the Core (Connecting Organizing Reflecting Extending) model on learning the moral creed does not rule out the possibility that it can be applied to other learning so that the teacher can make variations and liven up the classroom atmosphere as a facilitator, motivator, evaluator and informatory.